2022
DOI: 10.1101/2022.12.20.521286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of pyrimidine synthesis in murine skin wounds induces a pyoderma gangrenosum-like neutrophilic dermatosis accompanied by spontaneous gut inflammation

Abstract: Pyoderma gangrenosum (PG) is a debilitating skin condition often accompanied by inflammatory bowel disease (IBD). Strikingly, ~40% of patients that present with PG have underlying IBD, suggesting shared but unknown pathogenesis mechanisms. Impeding the development of effective treatments for PG is the absence of an animal model that exhibits features of both skin and gut manifestations. This study describes the development of the first experimental drug-induced mouse model of PG with concurrent intestinal infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Given emerging cases of primary immunodeficiency‐associated PG, the question of possible genetic predisposition to the development of PG may be raised. It has been suggested that elevated levels of pro‐inflammatory cytokines may serve as a second hit in the development of PG‐like inflammation caused by neutrophil extracellular trap (NET) formation 85 . It is interesting to consider whether the development of PG requires acquisition of a second pro‐inflammatory hit, and whether patients who have a primary immunodeficiency are more susceptible to developing PG due to an existing aberration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given emerging cases of primary immunodeficiency‐associated PG, the question of possible genetic predisposition to the development of PG may be raised. It has been suggested that elevated levels of pro‐inflammatory cytokines may serve as a second hit in the development of PG‐like inflammation caused by neutrophil extracellular trap (NET) formation 85 . It is interesting to consider whether the development of PG requires acquisition of a second pro‐inflammatory hit, and whether patients who have a primary immunodeficiency are more susceptible to developing PG due to an existing aberration.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that elevated levels of pro-inflammatory cytokines may serve as a second hit in the development of PG-like inflammation caused by neutrophil extracellular trap (NET) formation. 85 It is interesting to consider whether the development of PG requires acquisition of a second pro-inflammatory hit, and whether patients who have a primary immunodeficiency are more susceptible to developing PG due to an existing aberration. Further studies detailing the natural history of the disease as well as studies involving the inflammatory mechanisms of PG may prove useful in determining whether the inflammatory pathways and NETosis involved in PG require a second hit.…”
Section: Major Open Questionsmentioning
confidence: 99%
“…Dear Editor, Pyoderma gangrenosum (PG) is a chronic, ulcerative skin condition characterised by dysregulated responses of neutrophils, T cells, macrophages and fibroblasts to antigenic stimuli. 1 Our understanding of the aetiology of PG to guide targeted therapeutics has been hindered by a lack of validated animal models, with a murine skin model only recently established by Jatana et al 2 While this model is a valuable first step, this was only validated against known inflammatory cytokine/chemokine profiles of PG and has, therefore, not yet been used to discover novel molecular characteristics. As such, drug-induced PG remains a useful model to improve the understanding of PG pathophysiology via deciphering the molecular actions of causative medications.…”
Section: E T T E Rmentioning
confidence: 99%